Modelling snowfall in southern Italy: a historical perspective in the Benevento Valley (1645-2018) - Diodato, Nazzareno; Gómara Cardalliaguet, Íñigo; Bellocchi, Gianni (Climate Research, 2021)
© 2021 Inter-Research. The lack of long-term, homogeneous snowfall records is a limitation in environmental studies. Statistical modelling holds potential to extend snowfall records back in time with a limited set of predictors: snow severity and winter-spring temperatures (with their variability) to reflect elevation influences. The annual number of snow days (SDY) in the Benevento Valley (southern Italy) was detailed for the period 1870-2018. Calibrated in the period 1870-1968 (R-2 = 0.85) and validated in the period 1969-2018 (R-2 = 0.67), the model developed here enabled the reconstruction of a time-series of SDY between 1645 and 2018. This unique series (the longest in southern Italy) shows that SDY peaked during the Little Ice Age (until similar to 1850), dominated by cold air masses or characterized by winter seasons extending until May (1655, 1684, 1763 and 1830) or June (1620). After the change-point detected in 1866, the modelled SDY time-series declined rapidly (Modern Warming Period, 1867-2018). The atmospheric conditions that favoured snowfall in the Benevento Valley throughout the study period were generally associated with an anomalous high-pressure system located over northern-northwestern Europe and a low in the eastern Mediterranean. This configuration allowed the incursion of cold continental air from the east-northeast into southern Italy. Our results are consistent with similar studies of snowfall in other European and mid-latitude regions of the northern hemisphere. Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub